Thermally stimulated and dynamic effects in identification and study of carbon materials by Raman spectroscopy - S.I. Isaenko; T.G. Shumilova (Учёные записки Казанского университета: Серия Естественные науки)
In this paper, the aspects of studying micron-sized carbon material substances using Raman spectroscopy with laser excitation were discussed. The relevance of the study is determined by the fact that the positions of diagnostic lines in the Raman spectra of carbon materials are significantly affected as the analyzed sample region is heated during the process of spectra recording, thereby resulting in a shift of the diagnostic lines and bands, up to the burnout of the analyzed particle region or to the complete combustion of the sample. To assess the influence of the laser radiation power on the position of diagnostic lines in the Raman spectra of carbon materials, we studied the position of the lines depending on the laser power and sample size of both natural and man-made carbon phases of various structures: highly crystalline graphite, glassy carbon, cubic monocrystalline diamond, hexagonal monocrystalline diamond (lonsdaleite), and ultrananocrystalline diamond. The study was performed by Raman spectroscopy with the use of a high-resolution LabRam HR800 microspectrometer (Horiba, Jobin Yvon). For mono-, nano-, and ultrananocrystalline diamonds, a number of examples were provided to demonstrate that the exciting laser power during Raman spectroscopy measurements of carbon materials must be especially carefully monitored in particles of 10 μm or less in size. For highly crystalline graphite particles, the laser power must be controlled in samples smaller than 4 μm in size. When the Raman spectra were registered during the controlled laser heating, it was found that the samples of a black carbon variety between coal and diamond (described as togorite by V.A. Yezersky V.A. (1986)) had intergrowths of diamond and glassy carbon, a diamond core with a glass-like carbon shell. The results obtained show that the controlled use of the thermal effect of laser radiation can be helpful in identification of the detailed spectroscopic characteristics that occur during the intensive heating of samples, as well as in recovering mineral individuals from aggregates.